Die Freudlose Gasse - Pabst, Georg Wilhelm (Germany, 1925)
The film is not only one of the most important films of the Weimar Republic, it is also one of the most spectacular censorship cases of the era. It is a story from the inflationary period in Vienna in the years immediately after World War I offered enough dynamite for several muckraking novels: nouveau riches currency and stock market speculators who wallow in luxury, while homeless and unemployed Lumpenproletariat is living in barns.
Keywords: Documentary films